Traumatic ipsilateral acute extradural and subdural hematoma - Gupta, Rahul; Mohindra, Sandeep; Verma, Saurabh Kumar (Indian Journal of Neurotrauma, 2008)
We report a unique case of brain trauma, harboring acute extradural haematoma and subdural haematoma on the same side.
Keywords: extradural hematoma; head injury; ipsilateral; subdural hematoma